Design, synthesis, and application of electroactive reporters for nucleic acid biosensing - Tansil, Natalia Chendrawati (2008)
This thesis discusses the design, synthesis, and application of electroactive reporters for nucleic acid biosensing. The reporters are able to specifically recognize and sensitively report the hybridization of target nucleic acids to capture probes in an electrochemical biosensor. Three compounds were used in different detection schemes. In each scheme, direct detection was achieved by measuring the electroactivity of Os or Ru complex. Lower detection limits were obtained through various amplification strategies. The Os complex catalytically oxidizes ascorbic acid, leading to an amplified current signal in amperometry and a detection limit of 60 fM for oligonucleotide samples. The Ru complex catalytically oxidizes guanine bases, leading to an increase of peak current in cyclic voltammetry and a detection limit of 1.5 pM for TP53 cDNA. The EDOT moiety acts as ‘seeds’ that facilitates selective polymerization of poly(EDOT). Under controlled conditions, the amount of polymer deposited was positively related to target DNA concentrations as low as 20 pM.